Nature conservation in Polish agriculture under conditions of EU membership - Karol Kociszewski (Economic and Environmental Studies (E&ES), 2013)
The paper's aim is to assess effectiveness of the implementation of nature conservation measures in Polish agriculture. Environmental regulations influence main groups of Common Agricultural Policy instruments. In the I pillar of the policy, it refers to cross-compliance, in the II pillar it refers to agri-environmental programmes, the Natura 2000 payments and organic farming support. In Poland they are ineffectively implemented and insufficiently directed to nature conservation. This refers both to domestic environmental and agricultural policy. In some aspects they are not coordinated. This is connected with delay in construction of protection plans which are necessary for proper policy in the Natura 2000 network. Consequently, the specialized payments for farmers in the Natura 2000 network have not been implemented yet while the extent in which agri-environmental measures have been implemented is too small. Moreover, the system of control and certification in organic farming does not involve requirements referring to biodiversity. There are some deficiencies in biodiversity protection standards within domestic regulations of cross-compliance. In this situation, Polish agriculture could contribute to degradation of biological diversity in rural areas.
Keywords: 330; environment protection in agriculture; biodiversity; sustainable development of agriculture; agri-environmental programmes; rural development measures